A atuação do psicólogo na estratégia saúde da família : um olhar gestáltico - Diógenes, Juliana Maria Pereira (2014)
This work emerges from questions developed by the researcher in the course of his career, with an emphasis on experience in Gestalt Therapy (GT) and also Multidisciplinary Residency in Family and Community (RMSFC) Health. With theoretical and practical knowledge in both areas, proposes the construction of theoretical and conceptual bridges between them, trying to show the possible contributions that GT as a psychological approach can offer to psychologists working in the context of the Family Health Strategy (FHS). This is a research-driven qualitative approach, based on the proposed link between hermeneutics and dialectics, understanding that this discussion brings great contributions not only to how to do, but also how to think about the analysis of empirical material. A purposive sample includes residents psychologists and tutors related to Integrated Health Residency with Emphasis on Family and Community Health, School of Public Health of Ceará. For data collection, the use of semi-structured interviews was used. The categorization of the empirical material led to five central themes: the importance of psychological approaches, in general, for the psychologist in the ESF; visions of man and the world of humanistic approaches while guiding the work of the psychologist in the ESF; recovery by psychologists way of life of the subjects (individual or collective) and the demands stated by them; modes of intervention of the psychologist in the context of the ESF; and the theoretical and practical connections. Next, we sought to understand how these issues are close to concepts related to GT, the FHT and the Clinic Extended associating empirical themes to theoretical concepts. The results indicated that the Gestalt therapy has a good acceptance of psychologists working in the ESF, which can realize the vast majority of the contributions that this approach offers to its performance in this context. The main contribution of the GT, which will be the basis for all others, it is the starting point of a gestalt reasoning, is the vision of the whole human being, who proposed their understanding in all its dimensions. Therefore, it is recognized that the very demand for the ESF to work with an integrated view of a singular subject, where the person, family or community should be understood in its broader context, the psychologist just approaching the gestalt approach.